MODIFIKASI KEBAYA BER-BUSTIER LEKAT DENGAN SISTEM SOEN - Widiyanti, Eti; Wening, Sri; Budiastuti, Emy (Universitas Negeri Yogyakarta, 2023)
This research aim to (1) Knowing the process of making a modified bustier kebaya; (2) Knowing the effect of a modified bustier kebaya with a so-en system technique on the level of comfort in terms of the position of the kebaya fitting factor; (3) Knowing the most preferred modified kebaya by consumers. This research is a true experimental study with a post test only control design. The data collection technique used is through observation sheets and questionnaires (anget). The assessment was carried out by five panelists to find out the position of the kebaya fitting facto analysis technique used was an independent T-test conducted to see the effect of a modified bustier kebaya on the level of comfort in terms of the position of the fitting factor. The preference level test for the product was carried out through a questionnaire with 20 target user respondents. The results showed: Modified bustier fitting kebaya (Design 1) got an average score of 3.88 (VERY GOOD), modified bustier fitted fitting (Design 2) got an average score of 3.81 (VERY GOOD), and modified fitting with a bustier separately (Design 3) get an average value of 3.06 (GOOD). The most preferred modified kebaya product by consumers is Design 1 which shows that the average voter is 39%, Design 2 gets a score of 37% and Design 3 gets a score of 24%.